IMPROVING READING ACHIEVEMENT IN HARNETT COUNTY ELEMENTARY SCHOOLS THROUGH EARLY READING INTERVENTIONS: A PROGRAM EVALUATION OF READING RECOVERY AND LEVELED LITERACY INTERVENTION FOR FIRST GRADERS - Spivey, Jennifer (East Carolina University, 2019)
This program evaluation took place in Harnett County Schools, North Carolina. This study evaluated two common reading intervention programs currently used in the Harnett district. This evaluation compared and examined the effectiveness of Reading Recovery and Leveled Literacy Intervention on a subset of students at Highland Elementary School, a Title I School in Harnett County, North Carolina. The study revealed that first grade students who received Reading Recovery and Leveled Literacy Intervention for twelve weeks for remediation in the area of reading showed reading growth. Reading Recovery and Leveled Literacy Intervention reading intervention programs are both designed to be short term, intensive reading programs for students below grade level reading standards. Both programs include phonics instruction, phonemic awareness, reading comprehension strategies, writing, assessment and school/home connection. Reading Recovery is administered in a one-on-one setting by highly trained reading specialists and Leveled Literacy Intervention is administered in a small group of six students or less students by traditional first-grade teachers. The study concludes that Reading Recovery and Leveled Literacy Intervention are both effective interventions for first grade struggling readers.
Keywords: Reading Intervention; Reading Recovery and Leveled Literacy Intervention; Literacy programs--North Carolina--Harnett County; Reading--North Carolina--Harnett County; First grade (Education)--North Carolina--Harnett County